Studi Kelayakan Bisnis pada Usaha Pembuatan Batu Bata dari Bekas Tanah Galian di Desa Muara Pijoan Kabupaten Muaro Jambi - Hadi Pratama Ariansyah; Efni Anita; Neneng Sudharyati (Jurnal Riset Ekonomi dan Akuntansi, 2025)
This research, titled Business Feasibility Study of Brick Manufacturing from Excavated Soil in Muara Pijoan Village, Muaro Jambi Regency, is motivated by the challenges faced by craftsmen in managing brick production, particularly concerning the diminishing availability of clay raw materials and the necessity for products to comply with Indonesian National Standards (SNI). The study aims to comprehensively analyze the management of the business, operational costs, and the potential profits that can be obtained from brick manufacturing in the village. To achieve this objective, the research employs methods that include field observations and interviews with business operators, allowing the researcher to understand the production processes and management practices implemented in this venture. The research results show that the brick-making business in Muara Pijoan Village is managed efficiently, producing 20,000-40,000 bricks per cycle with a net profit of around 30%. Monthly operational costs reach Rp 10,000,000, including excavator rental and employee meals. This business is considered feasible, with the initial capital of Rp 40,000,000 already paid off, and its strategic location supports easy access. The production and quality of the bricks meet market demand, making this business have good prospects for future growth.